Paraplegia by spinal cord compression as the initial manifestation of Hodgkin’s disease: a case report - Baroni, Lorenza; Fornaciari, Sara; Predieri, Barbara; Bergonzini, Patrizia; Guerra, Azzurra; Paolucci, Paolo; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2014)
The 90% of Hodgkin’s disease (HD) cases are originated by lymphnodes whereas 10% by extranodal regions as epidural space. Neurologic complications of HD can be classified as directly resulting from the disease or indirectly originated from the disease or from its treatment. Patients very rarely present with spinal cord compression (SCC)  due to epidural HD. Few cases of HD with such presentation have been reported in the literature. Primary spinal extradural HD with no further organ involvement is extremely rare. We report a case of a child with SCC as initial and unique presentation of HD.